Practical dimension of local democracy. Model of cooperation of the City of Szczecin with non-governmental organizations - Kowalczyk, Krzysztof Andrzej (Political Preferences, 2017)
The aim of this article is to analyze the cooperation of the City of Szczecin with non-governmental organizations in the years 2012-2016. The article deals with the formal and legal aspects of cooperation, the potential of Szczecin NGOs, selected areas of co-operation within the three dimensions and conclusions. The hypothesis assumes that the City of Szczecin is a model example of cooperation with non-governmental organizations. Key words: local democracy, non-governmental organizations, city of Szczecin